2015
DOI: 10.1080/15384047.2015.1095402
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-622 acts as a tumor suppressor in hepatocellular carcinoma

Abstract: microRNAs (miRNAs) are important regulators of tumor development and progression. In this study, we aimed to explore the expression and role of miR-622 in hepatocellular carcinoma (HCC). We found that miR-622 was significantly downregulated in human HCC specimens compared to adjacent noncancerous liver tissues. miR-622 downregulation was significantly associated with aggressive parameters and poor prognosis in HCC. Enforced expression of miR-622 significantly decreased the proliferation and colony formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…They are broadly involved in a variety of biological functions of RCC development and progression including cell proliferation, metastasis, angiogenesis, drug resistance, metabolism and others [ 4 – 6 ]. MiR-622 plays an inhibiting role in various cancer like glioma [ 7 ], colorectal cancer [ 8 10 ], hepatocellular carcinoma [ 11 , 12 ], lung cancer [ 13 ], esophageal squamous cell carcinoma [ 14 ] and gastric cancer [ 15 ]. The biological functions of miR-622 in the reported cancers include cell proliferation and metastasis [ 7 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are broadly involved in a variety of biological functions of RCC development and progression including cell proliferation, metastasis, angiogenesis, drug resistance, metabolism and others [ 4 – 6 ]. MiR-622 plays an inhibiting role in various cancer like glioma [ 7 ], colorectal cancer [ 8 10 ], hepatocellular carcinoma [ 11 , 12 ], lung cancer [ 13 ], esophageal squamous cell carcinoma [ 14 ] and gastric cancer [ 15 ]. The biological functions of miR-622 in the reported cancers include cell proliferation and metastasis [ 7 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast and according to our findings on miR-622-mediated KRAS suppression which reduced proliferation, the growth-suppressive effects of miR-622 on HCC cells were only minimally affected by its effect on CXCR4 expression [141]. Song et al found that miR-622 negatively regulates mitogen-activated protein 4 kinase 4 (MAP4K4) in HCC but overexpression of MAP4K4 only partially reversed the growth-suppressive effects of miR-622 on HCC cells [142]. In a recent study, the same group also demonstrated that MAP4K4 promoted the epithelial-mesenchymal transition and invasiveness of HCC cells largely via activation of the c-Jun N-terminal kinase(JNK) and the nuclear factor "kappa-light-chain-enhancer" of activated B-cells (NF-κB) signaling [143].…”
Section: Microrna-622supporting
confidence: 58%
“…MiR-622 downregulation also unreleases its target CXCR4 which mediates migration of tumor cells [141]. Further, low miR-622 expression induces de-repression of MAP4K4 promoting epithelial to mesenchymal transition (EMT) and invasiveness [142,143]. Low levels of miR-26a in tumor cells lead to increased integrin α5 expression and reduced E-cadherin expression inducing EMT [144][145][146].…”
Section: The Let-7 Mirna Familymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, growth-suppressive effects of miR-622 on HCC cells were only slightly affected by its effect on CXCR4 expression 32. Song et al found that miR-622 negatively regulates mitogen-activated protein 4 kinase 4 (MAP4K4) in HCC, but overexpression of MAP4K4 only partially reversed the growth-suppressive effects of miR-622 on HCC cells 31. In a recent study, the same group demonstrated that MAP4K4 promotes the epithelial–mesenchymal transition and invasiveness of HCC cells largely via activation of c-Jun N-terminal kinases and nuclear factor kappa-light-chain-enhancer of activated B cells signalling 43.…”
Section: Discussionmentioning
confidence: 99%